Weight stigma in Australia: a public health call to action - Blake J Lawrence; Xochitl de la Piedad Garcia; James Kite; Briony Hill; Kelly Cooper; Stuart W Flint; John B Dixon (Sax Institute, 2022)
People living with obesity experience weight stigma in most social settings. This has a negative impact on their health and quality of life. A primary contributor to weight stigma is the misconception that obesity is caused by factors solely within an individual's control. However, this disregards the complex and multifaceted nature of obesity. Weight stigma is perpetuated by the media, healthcare practitioners and researchers, and even in public health campaigns and policies designed to help people living with obesity. This perspective article is a public health call to action to address weight stigma in Australia. We provide key recommendations for public health researchers, practitioners, and policy makers.